Μ-CALPAIN REGULATE CARDIOMYOCYTES APOPTOSIS VIA APOPTOSIS INDUCING FACTOR AND BID IN RAT HEART ISCHAEMIA/REPERFUSION INJURY. (8th October 2012) - Zhao-Feng, Song; Dong-Yu, Chen; Bo, Du; Li-Zhen, Wang; Fan, Wang; Xin-Yan, Qi; Qing-Hua, Zhou; Zhao-Feng, Song
Abstract : Objectives: Heart I/R may exacerbate myocardial injury by the release of massive of reactive oxygen and nitrogen species. Calpain has been proposed to play a role in the pathogenesis of heart I/R injury. However, the underlying mechanisms are still not thoroughly understood. Here we investigated the effect of μ-Calpain on heart I/R injury and elucidated the underlying mechanisms. Methods: Studies were performed with I/R rats' hearts. MDL-281703, a μ-Calpain inhibitor, was used to inhibit the activate of μ-Calpain. The cardiac function and cells apoptosis were detected. The activation of μ-Calpain, Bid and Apoptosis-inducing factor (AIF) were evaluated during the I/R protocol. Results: During the I/R protocol, the 76 kDa size of fragment, which was active fragment of μ-Calpain, significantly increased. In the same time, the expression of AIF in nuclear and Bid also increased. Administration of MDL-281703 decreased cells apoptosis from 36±3.9% to 25±7.1% p<0.05) and simultaneously improved the cardiac function. Administration of MDL-281703 also reduced the expression of Bid and attenuated mitochondrial-nuclear translocation of AIF. Conclusions: Our results suggested that μ-Calpain played a role of cells apoptosis in rats heart I/R injury. In this process, μ-Calpain regulate cardiomyocytes apoptosis via both caspase-dependent pathway (Bid) and non-caspase dependent pathway (AIF).